Changes in physical performance parameters during and after moderate altitude training in elite cross country skiers - Jensen, K.; Höök, M.; Willis, S.; Holmberg, H. C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The Olympic cross country skiing competitions in 2014 will be held in Sochi, Russia at an altitude of approximately 1500m. Although moderate, this altitude is known to reduce performance in highly trained endurance athletes. It is also known that individuals react differently during altitude exposure. The purpose of this study was to evaluate performance changes during and after three weeks of training in moderate altitude in elite skiers.